大跨径双层悬索桥钢桁梁整体焊接点疲劳分析与实验 = Fatigue analysis and test on integral welded joint at steel truss girder of long-span double deck suspension bridge - 邓晓光 Deng, Xiao-guang (2017)
为了给大跨径钢桁梁悬索桥抗疲劳设计提供依据，针对杨泗港长江大桥钢桁梁采用的整体焊接节点，开展了多轴疲劳荷载作用下整体焊接节点的有限元疲劳分析和试验研究。首先通过建立全桥有限元模型，基于英国BS 5400规范和Miner准则，获得了在标准疲劳车作用下全桥最不利整体节点及其各杆件200万次等效疲劳轴力幅；其次建立最不利整体节点空间精细化模型，通过对各轴向杆件施加200万次等效疲劳轴力幅，进行了多轴荷载下整体节点的疲劳性能分析；最后基于相似理论，设计了1：6的整体焊接节点缩尺模型，进行多轴荷载下的疲劳试验研究。结果表明：位于距主塔297 m距离的F34节点为疲劳最不利下弦杆整体节点；F34节点最大Von-Mises应力在78.8~130.6 MPa，小于设计规范的疲劳强度；200万次的模型疲劳加载试验过程中，未发现任何疲劳裂纹产生，各测点的应力值与理论值误差小于7.8%；杨泗港长江大桥钢桁梁整体焊接节点疲劳性能满足设计要求，研究成果对大跨径双层悬索桥抗疲劳设计具有直接的指导作用。To provide a reference for anti-fatigue design of long-span steel truss suspension bridge, aimed at integral welded joint adopted in Yangsigang Yangtze River Bridge, finite element analysis and test of integral welded joint under the multi-axial fatigue load were carried out. Firstly, in terms of BS 5400 specification and Miner criterion, the finite element model of whole bridge was established to obtain the most unfavorable integral joint under the standard fatigue vehicle, as well as the equivalent axial force amplitude of each member at integral joint when the cycle times reached two million. Secondly, a space refined model of the most unfavorable integral welded joint was built, and applying the equivalent axial force amplitude to each member, the fatigue performance of integral welded joint under the multi-axial fatigue load was analyzed. Finally, a fatigue test was carried out on a 1:6 scale model of integral welded joint on the basis of the similarity theory. The results show that the F34 node located at the distance of 297 m from the main tower is the most unfavorable integral joint at lower chord, and the maximum Von-Mises stress of the F34 node is between 78.8 MPa and 130.6 MPa, less than the fatigue strength stipulated in design specification. No cracks are detected in the test model after the two million cycles fatigue loading, and the max error between the measured and theoretical values is less than 7.8%. It can be seen that the fatigue performance of integral welded joint at steel truss girder of Yangsigang Bridge is reliable in anti-fatigue design, and the research results have a direct guidance to anti-fatigue design of long-span double-deck suspension bridge.